مقاربات في التنوّع السوسيوصواتة - Altaie, Nima D. (Al-Adab Journal, 2019)
Development of the law refers to the absolute change, as a universal law, is subject to that in the presence of phenomena, and appearances, and situations, and variations, whether material or social, or other. Language is not an exception to this law, which is at all levels prone to it; for the works which, leads to reproduction of one language into several variations accented, and its main reason is the difficulty of communication , interaction and connection between people of the same language, and do not socialize with each other; because of the conditions of the same language be the language spoken by users coherent; by taking a means of communication and expression needs and common purpose between the linguistic group. Hence we decide from the viewpoint of Sosiolinguistic that moving language, not static, but change and evolve always constantly , though not felt by many people ; because the change that infect comes slowly , and gradually , as development usually starts with individual creativity after that successful innovation, and commonly , acquired by the linguistic group concerned their use among people. Over time this new change becomes an integral part of the social language, and fundamental image, and this is like all linguistic evolution. When the sound is the basis for a series of variations accents; it became necessary for the research to study the genesis of the human being, and the modalities for the acquisition of a child under the umbrella of sociophonology, which is a branch of sociolinguistics in examining these grave accent differences noticed in its a social function. These differences are not a part of the specific language for one person, it is also common among groups of speakers, and then look into the causes of diversity and modes of sociophonology. Accordingly, the research is divided into two sections, namely:First language acquisition and its effect on its diverse accent.Sociophonological Diversity (contrastive analysis in concept and classification).Conclusions